M. de Caro-M. Mori-E. Spinelli (eds.), Libero arbitrio. Storia di una controversia filosofica, Carocci, Roma 2014 - Mazzetti, Manuel (Revista Archai, 2025)
M. de Caro-M. Mori-E. Spinelli (eds.), Libero arbitrio. Storia di una controversia filosofica, Carocci, Roma 2014